Avalia????o de riscos ambientais no gerenciamento de res??duos em setores assistenciais de um hospital p??blico na cidade de S??o Paulo - Urioste, Ariel (2019)
Proper management and handling of health service waste (HSW) are challenges experienced by hospitals and are complex because these wastes are made up of biological, chemical and radioactive materials. The challenges related to HSW refer to adequate management for the lowest possible environmental impact. In this context, it was verified the need to use a management tool with the objective of investigating the nonconformities found in the disposal and management of these wastes in the care areas of a public hospital. For this the tool called Failure Mode and Effect Analysis or FMEA was selected. This tool has been gaining ground in assessments of adverse environmental impacts, particularly in the assessment of environmental risks in health care facilities. In this context, the objective of this research was to evaluate the use of the FMEA in Surgical Center, Birth Center and Surgical Clinic of a hospital located in the city of S??o Paulo, as an instrument to evaluate the risk of managing HSW generated. For the execution of the study, we used mixed methods such as cross - sectional research and the use of a case study, to consolidate the information with data collection with triangulation of sources through documentary analysis, interview and participant observation. The results of the FMEA show flaws in waste management, in which 32% of the interviewees erred in at least one question, indicating risks and critical points in the incorrect segregations performed by the nursing professionals, even though the interviewees believe they have enough knowledge and skills to do correct HSW management. It was possible to identify better results related to the attitude of segregation of the professionals with complete upper level and postgraduates. It is concluded that the FMEA tool contributed to identify nonconformities, listing actions according to their priorities and facilitating decision makers. It is recommended to extend the study to other care sectors as well as to reach the medical teams, to understand how HSW management is carried out by this group of professionals.